1982
DOI: 10.1111/j.1095-8649.1982.tb03922.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative tolerance to gas supersaturated water of carp, Cyprinus carpio, and black bullhead, Ictalurus melas, from the U.S.A. and Italy

Abstract: Supersaturation of surface water with atmospheric gases may result from hydroelectric or thermoelectric power generation and adversely affect aquatic biota. Although the phenomenon has been extensively studied in the northwestern United States, its occurrence is less well documented in Europe. We evaluated the tolerance ofcarp, Cyprinus carpio, and black bullhead, Ictalurus melas, from Italy to gas supersaturated water and compared our results to data reported in the literature for the same species from the Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Fickeisen et al (1976) estimated that the 96-h LL50 for adult black bullheads Ameiurus melas (formerly Ictalurus melas) occurred over a temperature range of 8-20°C at 123.8-126.7% total gas pressure (estimated AP = 181-203) in water 35 cm deep. Also, Gray et al (1982) estimated that the 96-h LL50 in common carp Cyprinus carpio TABLE 6.-Percentages of 46-mm (total length) juvenile lake trout with signs of gas bubble disease at different gas supersaturation levels. Gas supersaturation was measured as total gas pressure above equilibrium (AP, in mm Hg).…”
Section: Discussionmentioning
confidence: 99%
“…Fickeisen et al (1976) estimated that the 96-h LL50 for adult black bullheads Ameiurus melas (formerly Ictalurus melas) occurred over a temperature range of 8-20°C at 123.8-126.7% total gas pressure (estimated AP = 181-203) in water 35 cm deep. Also, Gray et al (1982) estimated that the 96-h LL50 in common carp Cyprinus carpio TABLE 6.-Percentages of 46-mm (total length) juvenile lake trout with signs of gas bubble disease at different gas supersaturation levels. Gas supersaturation was measured as total gas pressure above equilibrium (AP, in mm Hg).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas many of the symptoms of GBT in fish have been identified, determining the relationships between TDG supersaturation and effects on fish is complicated by the many factors that modify the severity of GBT. Intrinsic factors that affect the severity of GBT can include body size (Krise & Herman, 1991; Rucker, 1975; Shrimpton et al., 1990a), life stage (Bouck, Nebeker, & Stevens, 1976; Counihan et al., 1998; Geist et al., 2013), species (Bouck et al., 1976; Dawley, Monk, et al., 1976; Mesa, Weiland, & Maule, 2000), and possibly stock (Gray, Page, & Bronzi, 1982) and behaviour. Extrinsic factors such as depth (Antcliffe, Fidler, & Birtwell, 2002; Fickeisen & Montgomery, 1978; Pleizier, Nelson, Cooke, & Brauner, 2020), temperature (Ebel, Dawley, & Monk, 1971; Fickeisen, Montgomery, & Hanf, 1974; Nebeker, Hauck, & Baker, 1979) and oxygen‐to‐nitrogen ratios (Jensen, 1988; Nebeker, Bouck, & Stevens, 1976; Nebeker et al., 1979) have also been demonstrated to affect GBT.…”
Section: Introductionmentioning
confidence: 99%
“…Random intercepts for each individual indicated that there was important inter‐individual variation in depth use and the risk model corroborated this with random intercepts also indicating that some fish were more prone to exposure to total dissolved gas supersaturation than others. There may also be some evolutionary pressures on fish living in rivers such as Rysstad where total dissolved gas supersaturation has been present for several decades that selects for genes or phenotypes that are resilient to supersaturation; Gray et al (1982) suggested that higher supersaturation tolerance among Columbia River fish compared to controls from Italy might reflect a legacy of exposure in the Columbia. Cyprinids have better physiological tolerance to total dissolved gas supersaturation than salmonids (e.g., Fan et al, 2020; Wang et al, 2015), but what the mechanisms and whether they are heritable could be revealed in experiments and could include some experimental displacement field studies by transporting, tagging and observing behaviour and survival of fish from an affected and unaffected area.…”
Section: Discussionmentioning
confidence: 99%